Zebrafish Model for Nonsyndromic X‐Linked Sensorineural Deafness, DFNX1. Issue 3 (7th April 2019) - DeSmidt, Alexandra A.; Zou, Bing; Grati, M'hamed; Yan, Denise; Mittal, Rahul; Yao, Qi; Richmond, Michael T.; Denyer, Steven; Liu, Xue Zhong; Lu, Zhongmin
ABSTRACT: Hereditary deafness is often a neurosensory disorder and affects the quality of life of humans. Only three X‐linked genes (POU class 3 homeobox 4 ( POU3F4 ), phosphoribosyl pyrophosphate synthetase 1 ( PRPS1 ), and small muscle protein X‐linked ( SMPX )) are known to be involved in nonsyndromic hearing loss. Four PRPS1 missense mutations have been found to associate with X‐linked nonsyndromic sensorineural deafness (DFNX1/DFN2) in humans. However, a causative relationship between PRPS1 mutations and hearing loss in humans has not been well studied in any animal model. Phosphoribosyl pyrophosphate synthetase 1 (PRS‐I) is highly conserved in vertebrate taxa. In this study, we used the zebrafish as a model to investigate the auditory role of zebrafish orthologs ( prps1a and prps1b ) of the human PRPS1 gene with whole mount in situ hybridization, reverse transcription polymerase chain reaction, phenotypic screening, confocal imaging, and electrophysiological methods. We found that both prps1a and prps1b genes were expressed in the inner ear of zebrafish. Splice‐blocking antisense morpholino oligonucleotides (MO1 and MO2) caused exon‐2 skip and intron‐2 retention of prps1a and exon‐2 skip and intron‐1 retention of prps1b to knock down functions of the genes, respectively. MO1 and MO2 morphants had smaller otic vesicles and otoliths, fewer inner ear hair cells, and lower microphonic response amplitude and sensitivity than control zebrafish. Therefore, knockdown of either prps1a or prps1b resulted in significant sensorineural hearing loss in zebrafish. We conclude that the prps1 genes are essential for hearing in zebrafish, which has the potential to help us understand the biology of human deafness DFNX1/DFN2. Anat Rec, 303:544–555, 2020. © 2019 American Association for Anatomy